Networks of Governance: Users, Platforms, and the Challenge of Networked Media Regulation - Crawford, Kate; Lumby, Catharine (International Journal of Technology Policy and Law, 2013)
We conducted a study of Australia’s media content regulation system in the context of three major Federal Government reviews of media law and policy (Australian Law Reform Commission, 2012; Department of Broadband, Communications and the Digital Economy, 2012; Finkelstein, 2012). The current system understands governance as the work of government and industry, and either minimises or overlooks the role of users, the context of platforms, and the scope of participation. In this article, we assess the weaknesses in the current framework, and look both critically and pragmatically at the role users can play in media content governance. By drawing on the Australian situation as a case study, we consider the wider problem of governance within networked media spaces and the tensions between users, algorithms, platforms, industries, and nation states. Finally, we argue for the development of stronger theoretical model of ‘civic media governance’, based on principles of radical pluralism that can better account for dissent and dissonance.